Comercio electrónico, oportunidades y amenazas para las pymes del departamento de Boyacá – Colombia durante el periodo 2015-2018 (2021)
Describe how the behavior of electronic commerce has been during the period 2015-2018 in the municipalities of Duitama, Sogamoso and Tunja. Show the opportunities of new technologies used by SMEs for the use of electronic commerce.